Subcutaneous soft tissue metastases from esophageal squamous cell carcinoma with neuroendocrine differentiation: Case report and literature review - Geng, Xiaotao; Liu, Jie; Sun, Huimin; Song, Zhenguo; Qin, Shaoyong; Li, Yang; Zhang, Yanan; Hao, Furong; Cai, Yuanyuan (Frontiers in Oncology, 2022)
Background Esophageal squamous cell carcinoma is the predominant subtype of esophageal cancer in China and so differs from presentations in Western countries. Common metastatic locations of esophageal cancer include the liver, lung, bone, and brain. In contrast, metastases in subcutaneous soft tissue are exceedingly rare. Case presentation We present the experience of a 57-year-old man with a complaint of hand and leg dysfunction on the right side. He had a past medical history of esophageal squamous cell carcinoma. Further imaging workup revealed a solitary brain metastasis, thickening of the esophageal wall, swollen lymph nodes in the mediastinum, and right adrenal gland metastasis. Gamma knife radiosurgery of the brain metastasis and intensity-modulated radiotherapy of the esophagus and lymph nodes were administered. After 1.5 months, he was admitted to our hospital again, and nodules were identified in the anterior abdominal wall and left posterior chest wall. Ultrasound, CT, and radical excision of the abdominal wall mass were undertaken and revealed metastatic squamous cell carcinoma with neuroendocrine differentiation. We administered immunotherapy followed by targeted therapy. A PET/CT scan was performed to identify other organ metastases; the scan revealed multiple areas of fluorodeoxyglucose uptake and foci in the esophagus, lung, liver, bone, and right adrenal gland; and in various lymph nodes. In addition, an intensely hypermetabolic lesion was localized in the left posterior thorax. Conclusion This case highlights the diagnosis and treatment of uncommon metastases of esophageal squamous cell carcinoma. We hope that our clinical experience provides insights into these uncommon metastases.